EFFECTIVENESS OF LOW VERSUS HIGH DOSE STATINS FOR REDUCING MAJOR CARDIOVASCULAR EVENTS: A SYSTEMATIC REVIEW AND META-ANALYSIS: EFEKTIVITAS STATIN DOSIS RENDAH DAN TINGGI TERHADAP KEJADIAN KARDIOVASKULAR MAYOR: SUATU TINJAUAN SISTEMATISDAN META-ANALISIS - Khairuman Fitrah Ananda; Abigail Christine Sarumpaet; Agustina Sianturi (Faculty of Medicine Universitas Islam Sumatera Utara, 2026)
Coronary heart disease (CHD) remains a leading cause of global mortality. Statins are first-line therapy for reducing major adverse cardiovascular events (MACE); however, the optimal dosing strategy remains debated, particularly between ACC/AHA guidelines recommending high-dose statins and ESC guidelines favoring a stepwise approach. Asian populations with SLCO1B1 gene polymorphisms are at increased risk for statin-related adverse effects, such as myopathy and hepatotoxicity. This study aimed to assess the efficacy and safety of high-dose versus low-dose statins in reducing MACE among patients with coronary artery disease (CAD). Methods: A systematic review and meta-analysis were conducted following PRISMA 2020 guidelines. Literature searches were performed in PubMed, Embase, Cochrane Library, and Scopus (2020–2025). Ten studies (n = 43,985) were included in the final analysis. Random-effects meta-analysis was performed using Review Manager 5.4. Funnel plot asymmetry suggested potential publication bias. High-dose statins significantly reduced MACE risk (RR 0.85; p = 0.004) and LDL-C levels, but increased myopathy (OR 2.3) and hepatotoxicity risks, especially in SLCO1B1 polymorphism carriers. Low-dose statins plus ezetimibe achieved comparable LDL-C reduction with fewer adverse events. High-dose statin therapy significantly increased the relative risk of myopathy (OR 2.3; 95% CI 1.8–2.9), particularly in genetically susceptible individuals. Conclusion: High-dose statins improve cardiovascular outcomes but require close monitoring. Low-dose statins with ezetimibe offer a safer alternative, supporting personalized therapy based on genetic and clinical factors.